Climate scientists need to set the record straight: There is a scientific consensus that human‐caused climate change is happening. (7th May 2014) - Maibach, Edward; Myers, Teresa; Leiserowitz, Anthony
Abstract Nearly all climate scientists are convinced that human‐caused climate change is occurring, yet half of Americans do not know or do not believe that a scientific consensus has been reached. That such a large proportion of Americans do not understand that there is a near‐unanimous scientific consensus about the basic facts of climate change matters, a lot. This essay briefly explains why, and what climate science societies and individual climate scientists can do to set the record straight.